HUBUNGAN PENGARUH RELASI MAHASISWA DENGAN MAHASISWA DAN KADAR HAEMOGLOBIN (HB) DENGAN PRESTASI BELAJAR MAHASISWA TINGKAT II PRODI D III KEBIDANAN STIKes RANAH MINANG PADANG - Winarni Eka Mayasari (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2016)
Based on the learning process in Prodi DIII Midwifery there is a decrease in student learning achievement in level II. It can be seen from the drop in grade point average (GPA) students of the first semester and the second semester. There was a decrease prtestasi learned from the first half with honors as many as 18 people and a decline in the second half as many as 15 people. The purpose of this study was to determine the relationship influence student relationships with students and Hb with student achievement level II Prodi DIII Midwifery STIKes Minang Padang in 2015. This type of research is analytic with cross sectional study design. The population in this study were all students of level II Prodi DIII Midwifery totaling 33 people. The sampling technique is total sampling. Data were collected using a questionnaire on 10 to 16 August 2015. The univariate analysis is shown in the form of a frequency distribution table and bivariate analysis shown by the results of the chi square test. The results showed 36.4% of students had Hb levels of anemia. 57.6% of students have influence student relationship with a student. 36.4% of the students have learning achievement is not satisfactory. There is a relationship between students and student relationships with the student learning outcomes. There is a relationship between Hb and students with student learning outcomes at level II Prodi DIII Midwifery STIKes Minang Padang 2015. There are students with student relationships and hemoglobin (Hb) and academic achievement in students. Students are expected to follow the existing regulations in the dorms and are expected to support each student with a friend in increased learning achievement.